#TITLE_ALTERNATIVE# - SRI DORA BR DAMANIK (NIM : 13706049); Pembimbing : Dr. Ir. Aditianto Ramelan , DINA
Low Density Porous Concrete (LDPC), known as Aerated Concrete in industrial market, is classified as a lightweight concrete. This type of concrete is produced by entrapping air inside the concrete. The density of autocaved LDPC is about 400 Ã‚Â– 700 kg/m3. The essential feature of insulating concrete is its coefficient of thermal conductivity must be below 0.3 W/mK, whilst the density is generally less than 800 kg/m3. The main raw materials used in this research were cement, fly ash, CaO (lime), and water with the variation of water-cement ratio were 0.8, 1, 1.2, and 1.4. Besides, there was also a variation in the use of aluminium paste as the expanding agent. This variation with 7 days cured at atmospheric condition will affect the density, thermal conductivity, and pore homogeneity of the samples. Compound identification and pore distribution were analyzed by means of X-Ray Diffraction technique and macro-photography, respectively. Moreover, other characterizations were done such as density measurement and thermal conductivity test in order to assess physical and thermal properties of the samples. The results showed that the linearity between water-cement ratio towards density and thermal conductivity didn't occur at all of the test points. Samples with aluminum paste set 2 had lower density as well as an increasing watercement ratio.. Samples with aluminium paste set 1 had a lower thermal conductivity as well as an increasing water-cement ratio at two test points. The lowest density was 0.65 g/cm3 while the thermal conductivity was 0.37 W/mK. Pore homogenity can affect the conduction mechanism inside the concrete.